Training a Christian public health workforce: A qualitative study of Christian public health training programs - Jason Paltzer (Christian Journal for Global Health, 2018)
Objective: The objective of this qualitative pilot study was to identify opportunities and challenges Christian public health training programs experience when it comes to equipping public health students to work within Christian health mission organizations. Methods: A sample of seven out of seventeen (41 percent response rate) primarily American Christian public health institutions completed an online survey. Thematic analysis was conducted to identify major themes in the following areas: values specific to a Christian worldview, competencies focused on integrating a Christian worldview, challenges to integrating a Christian worldview, and training available to students interested in Christian health missions. Results: Values focused on Christ-like humility in serving God and others, discipleship, respecting human dignity in the image of God, and collaborative community partnership. More than half of the respondents identified the interrelationship between culture, religion, spirituality, and health as the primary competency integrating a Christian worldview. Global health was identified as the second competency followed by understanding the history and philosophy behind global health and missions. Identified challenges include faith of students and faculty, limited availability of Christian public health textbooks, and secularization of concepts such as poverty and development. Conclusion: The holistic nature of public health is conducive to integrating a Christian worldview into program content. The results show that Christian public health institutions have biblical values and integrate a Christian worldview in understanding the interrelationship between culture, religion, spirituality, and health primarily through the lens of global health. Programs experience significant challenges to embedding a Christian perspective into other content areas. Opportunities for integrating competencies with a Christian worldview include offering a certificate in global health/development ministry, teaching methods for engaging individuals and groups in holistic health discussions, and incorporating spiritual metrics and instruments into program evaluation courses to measure the influence of faith, hope, and discipleship alongside physical and social health metrics.